Understanding the Multifaceted Roles of Families in Caring for Palliative Patients in the Community: A Systematic Literature Review - Israfil Israfil; Ni Luh Putu Inca Buntari Agustini; I Gede Putu Darma Suyasa; Portia Zoleta- Vitug (JURNAL INFO KESEHATAN, 2026)
Enhancing family support in community-based palliative care is a growing global priority given the family's role as the primary caregiver for long-term palliative care patients in the community. This is a systematic literature review that aimed to synthesize recent evidence on the roles and contributions of families in caring for palliative patients in the community. A literature search was conducted through PubMed and ScienceDirect databases using the keywords “family role” OR “family support” AND “palliative” OR “palliative care.” The PEO framework guided the selection process, focusing on Population: families of palliative patients; Exposure: family caregiving roles; and Outcome: fulfillment of palliative care needs. Nine articles published between 2020 and 2025 met the inclusion criteria. The review identified diverse and interrelated family roles, including providing emotional and social support, delivering direct care, coordinating with healthcare professionals, engaging in decision-making and communication, and facilitating health education. Families also carried significant social and cultural responsibilities while adopting protective and adaptive coping strategies. The findings highlight that families are not merely companions but act as care managers, communicators, and educators who critically influence the quality of home-based palliative care. A unique insight from this review is the emphasis on the transitional phase from hospital to home as a crucial period requiring enhanced family capacity, structured coordination, and psychosocial support. Strengthening family education, telemedicine-based coordination, and community linkages emerges as a vital strategy to ensure holistic and sustainable palliative care delivery within community settings. Community nurses need to involve and meet the needs of families as clients in a nursing care plan that does not only focus on the needs of palliative patients